Micrometeorological Parameter and Energy Balance over Soybean - Khan, A; Nahar, BS; Hossain, MM; Baten, MA (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the Environmental Science Field Laboratory, Bangladesh Agricultural University, Mymensingh, to investigate the micrometeorological parameters such as air temperature, relative humidity, soil temperature, light intensity, solar radiation, photosynthetic active radiation (PAR), albedo and energy balance components over soybean field. Air temperature, solar radiation, light intensity were lower at the early morning hours, which gradually increased with the advancement of time and peaked at 13:00 hours, immediate after13:00 hours those value gradually declined. On the other hand air temperature and relative humidity were negatively correlated i.e. with the increase of air temperature, the relative humidity decreased. Soil temperature were measured at 2,5 and 10 cm depth and found that there was a distinct variation between 2 and 10 cm depth. Whereas, there was a small variation between 5 and 10 cm depth. Albedo level range from 0.18 to 0.24 and average value was 0.21 at midday. The energy balance components were measured using Bowen Ratio Energy Balance (BREB) method. On an average latent heat flux (LE) was 69 to 93% and ground heat flux (G) was 7 to 29% of the total Rn. Sensible heat flux (H) showed the negligible values due to wet soil surface and high soil moisture. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22147 J. Environ. Sci. & Natural Resources, 7(1): 69-74 2014